2017
DOI: 10.1128/aem.02747-16
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of a Select Mixture of Bacillus Probiotics Affects the Gut Microbiota and Goblet Cell Function following Escherichia coli Challenge in Newly Weaned Pigs of Genotype MUC4 That Are Supposed To Be Enterotoxigenic E. coli F4ab/ac Receptor Negative

Abstract: Structural disruption of the gut microbiota and impaired goblet cell function are collateral etiologic factors in enteric diseases. Low, moderate, or high doses of a Bacillus licheniformis-B. subtilis mixture (BLS mix) were orally administered to piglets of genotype MUC4 that are supposed to be F4-expressing enterotoxigenic Escherichia coli strain (F4 ϩ ETEC) F4ab/ac receptor negative (i.e., MUC4-resistant piglets) for 1 week before F4 ϩ ETEC challenge. The luminal contents were collected from the mucosa of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
80
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 54 publications
4
80
2
1
Order By: Relevance
“…Here, we also found that 4.5 g/kg of B. licheniformis-fermented products could reduce the number of Lactobacillus species in the feces of weaning piglets compared to the feces of piglets fed 1 g/kg of B. licheniformis-fermented products. In addition to the number of Lactobacillus species, the abundance of phylum Proteobacteria was increased in response to high-doses of Bacillus species-based probiotics treatment in the feces of weaning piglets challenged with F4 + ETEC [27]. Similar results were also observed in the fecal content of the group that was fed 4.5 g/kg of B. licheniformis-fermented products in the current study.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Here, we also found that 4.5 g/kg of B. licheniformis-fermented products could reduce the number of Lactobacillus species in the feces of weaning piglets compared to the feces of piglets fed 1 g/kg of B. licheniformis-fermented products. In addition to the number of Lactobacillus species, the abundance of phylum Proteobacteria was increased in response to high-doses of Bacillus species-based probiotics treatment in the feces of weaning piglets challenged with F4 + ETEC [27]. Similar results were also observed in the fecal content of the group that was fed 4.5 g/kg of B. licheniformis-fermented products in the current study.…”
Section: Discussionsupporting
confidence: 83%
“…Dietary supplementation of B. licheniformis in combination with B. subtilis reprograms the microbiota of weaning piglets challenged with F4 positive enterotoxigenic E. coli. strain (F4 + ETEC) [27]. Low-doses of Bacillus species-based probiotics also increase the number of Lactobacillus species in the feces of weaning piglets challenged with F4 + ETEC, while high-doses of Bacillus species-based probiotics have a negative impact on the number of Lactobacillus species [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, 10 rats selected randomly from each group (10/36) were placed in metabolic cages to measure body weight, blood glucose and urine volume. All experimental procedures were compliant with the Guidelines for Laboratory Animal Use and Care from the Chinese Center For Disease Control and Prevention and the Rules for Medical Laboratory Animals from the Chinese Ministry of Health, under protocol CAU-AEC-2013-073 (16) and were approved by the Ethical Committee of Qilu Hospital of Shandong University (Jinan, China; permit no. DWLL-20B-025).…”
Section: Animals and Drugsmentioning
confidence: 99%